(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Mirpur Thana, located in the northwestern part of Dhaka Metropolitan Area (DMA) is one of the most affected areas of fire in the RMG factories due to a large number of factories are operating in this area. Fire in the RMG sector has become a very common event in the recent years and causing colossal damage of lives and properties. The ultimate victims of fire in the factories are RMG workers because they become dead and injured and their livelihood held back. The present study based on the primary field investigation (including open ended questionnaire interview with a total of 70 workers), key informant interviews attempts to identify workers opinions on fire hazard issues and to understand the consequences, of how these problems become linked with the workers issue. J. Asiat. Soc. Bangladesh, Sci. 42(1): 77-93, June 2016